Place et rôle de l'enseignement de l'art dramatique au Québec : prospectives pour un monde en transformation - Francine Chaîné; Chantale Lepage; Carole Marceau (Université de Provence, 2021)
Drama has been taught for over 50 years in the Quebec school system. As early as 1969, the Rapport Rioux claimed the importance of art in school through "artistic doing and contact with works of art" (Rioux, 1969, vol. 2, p. 20). This seminal paper was the starting point for a series of drama programs. This essay takes a retrospective look at the evolution of the Quebec drama model, but it also tries to anticipate how learning and teaching theatre at school can contribute to the student citizen training who is creative, open mind, and responsible and, consequently equip them to better face a complex and uncertain world. In the evolution of practice, we also targeted the pedagogical approaches and the professional action of the artist teacher which contribute to the development of transformative skills in the drama classroom. Three professors carried out this essay and, they are involved in the drama training teachers.